2023
DOI: 10.1128/spectrum.04262-22
|View full text |Cite
|
Sign up to set email alerts
|

A Unique m6A-Dependent Restriction Endonuclease from an Archaeal Virus

Abstract: Many modification-dependent restriction endonucleases (MDREs) were identified in prokaryotes and recognized modified cytosine bases, such as 5-methylcytosine (5mC), 5-hydroxymethylcytosine (5hmC), and glucosyl-5-hydroxymethylcytosine (g5hmC). The first virus-derived MDRE (HHPV4I) from the archaeal virus HHPV4 was identified in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…Some known wH domains are adenine methylation (6mA)-specific. This notion was originally suggested by the demonstration of 6mA specificity of the DpnI wH domain and further strengthened by the observation of adenine specificity of the wH domain of HHPV4I (Lu et al, 2023), which was reported when this study was being finalized. In the hope of finding new adenine methylation-specific endonucleases, we searched for fusions of wH domains with endonuclease domains known to play roles in R-M (Pingoud and Jeltsch, 2001).…”
Section: Bioinformatic Screen Of Wh Domain Endonucleasesmentioning
confidence: 54%
See 4 more Smart Citations
“…Some known wH domains are adenine methylation (6mA)-specific. This notion was originally suggested by the demonstration of 6mA specificity of the DpnI wH domain and further strengthened by the observation of adenine specificity of the wH domain of HHPV4I (Lu et al, 2023), which was reported when this study was being finalized. In the hope of finding new adenine methylation-specific endonucleases, we searched for fusions of wH domains with endonuclease domains known to play roles in R-M (Pingoud and Jeltsch, 2001).…”
Section: Bioinformatic Screen Of Wh Domain Endonucleasesmentioning
confidence: 54%
“…6× His-tagged HhiV4I (see Supplementary Figure S5 ) was subjected to three-step chromatography (Ni-agarose column, DEAE column, and Heparin agarose column). Compared to the recently published paper on the same enzyme ( Lu et al, 2023 ), two additional chromatography steps were used (DEAE and Heparin columns). Unfortunately, the Heparin agarose chromatography step was less efficient for purification than is typical for other DNA-binding proteins because HhiV4I was in the flow-through and did not bind to the Heparin column, as would be expected for a typical nucleic acid-binding protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations